ASSESSMENT OF AWARENESS AND KNOWLEDGE REGARDING EYE DONATION AMONG MEDICAL AND NON-MEDICAL STUDENTS AROUND OUR HOSPITAL REGION (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Corneal blindness is a major public health problem and one of the leading causes of visual impairment worldwide. Eye donation remains the only effective means of obtaining donor corneas for corneal transplantation and restoration of vision. Awareness and knowledge regarding eye donation among young adults are essential for improving donation rates. This study was conducted to assess and compare the awareness and knowledge regarding eye donation among medical and non-medical students. Methodology: A cross-sectional questionnaire-based study was conducted in the Department of Ophthalmology, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from March 2024 to February 2025. Undergraduate medical and non-medical students were included after obtaining informed consent. Data were collected using a pretested, semi-structured self-administered questionnaire comprising 21 questions related to awareness, knowledge, sources of information, and willingness toward eye donation. Data were analyzed using SPSS version 25.0, and statistical significance was considered at p